Antecedents of Accountability in Village Fund Management - Safitri, Hilda; Respati, Novita WeningTyas (AJAR, 2025)
In the study, re-testing factors that are thought to have an impact on the accountability of village fund management was carried out. The purpose of the study was to test the influence of Community Participation, Use of Information Technology, Competence of Village Apparatus, and Internal Control System on the Accountability of Village Fund Management. The object of the study was a village device in Astambul Subdistrict of Astambul District. The population in the study numbered 308. Sampling using judgment sampling. The number of samples analyzed was 150 respondents. Primary data was collected through questionnaires that were directly directed to the respondents. Test the hypothesis using multiple linear regression. The results of the study show that community participation has no impact on the accountability of village management. However, the use of technology, the competence of the village apparatus, and the internal control system have a positive impact on the accountability of the management of the Village Fund. The research is expected to be input, information and consideration for village administration, for example by adding means of community aspiration, maximum use of information technology, procurement of seminars and training, and carrying out an inventory of village assets.